Plant Metaphors in the Old Greek of Isaiah - Austin, Benjamin M. (Septuagint and Cognate Studies, 2019)
Cover -- Contents -- Preface -- Abbreviations -- Introduction and Methodology -- Parts of Plants -- Kinds of Plants -- Conclusions -- Bibliography -- Ancient Sources Index -- Modern Authors Index